Hand hygiene to reduce community transmission of influenza and acute respiratory tract infection: a systematic review. Issue 5 (8th October 2012) - Warren‐Gash, Charlotte; Fragaszy, Ellen; Hayward, Andrew C.
Abstract : Please cite this paper as: Warren‐Gash et al. (2012) Hand hygiene to reduce community transmission of influenza and acute respiratory tract infection: a systematic review. Influenza and Other Respiratory Viruses DOI: 10.1111/irv.12015. Hand hygiene may be associated with modest protection against some acute respiratory tract infections, but its specific role in influenza transmission in different settings is unclear. We aimed to review evidence that improving hand hygiene reduces primary and secondary transmission of (i) influenza and (ii) acute respiratory tract infections in community settings. We searched Medline, Embase, Global Health and Cochrane databases up to 13 February 2012 for reports in any language of original research investigating the effect of hand hygiene on influenza or acute respiratory tract infection where aetiology was unspecified in community settings including institutions such as schools, and domestic residences. Data were presented and quality rated across outcomes according to the Grading of Recommendations Assessment, Development and Evaluation system. Sixteen articles met inclusion criteria. There was moderate to low‐quality evidence of a reduction in both influenza and respiratory tract infection with hand hygiene interventions in schools, greatest in a lower–middle‐income setting. There was high‐quality evidence of a small reduction in respiratory infection in childcare settings. There was high‐quality evidence for a large reduction in respiratory infection with a hand hygiene intervention in squatter settlements in a low‐income setting. There was moderate‐ to high‐quality evidence of no effect on secondary transmission of influenza in households that had already experienced an index case. While hand hygiene interventions have potential to reduce transmission of influenza and acute respiratory tract infections, their effectiveness varies depending on setting, context and compliance.